Discovery of a novel long terminal repeat (LTR2i_SS) in Sus Scrofa. (12th March 2014) - Lim, Sim L.; Kortschak, R. Daniel; Adelson, David L.
Summary Long terminal repeat (LTR) retrotransposons are transposable elements flanked by 5′/3′ LTRs. They have a structure similar to endogenous retroviruses, but they lack the envelope (env) gene making them non‐infectious. Long terminal repeats are motif‐rich sequences and can act as bidirectional promoters or enhancers to regulate or inactivate genes by insertion. In this study, we identified a new chimeric LTR subfamily, LTR2i_SS, in the pig genome. This chimeric LTR family appears to be the ancestral form of the previously described LTR2_SS family. LTR2_SS appears to have deleted 300 bp of un‐annotated, ancestral sequence from LTR2i_SS. We identified no functional provirus sequences for either of these LTR types. LTR2i_SS sequences have been exapted into the untranslated regions of two protein‐coding gene mRNAs. Both of these genes lie within previously mapped pig quantitative trait loci.